A Review on Aflatoxins Reduction in Food - Maryam Jalili (Iranian Journal of Health, Safety and Environment, 2016)
Aflatoxins (AFs) are cancerous secondary metabolites produced primarily by Aspergillus flavus and Aspergillus parasiticus in agricultural foodstuff such as peanuts, maize grains, cereals, and animal feeds. Food and Agricultural organization (FAO) estimated that as much as 25% of the world's agricultural commodities are contaminated with mycotoxins, leading to significant economic losses. Moreover, AFs are highly toxic, mutagenic, teratogenic and carcinogenic. Therefore AFs reduction in food and feedstuffs is a major global concern. This review aims to bring up to date the detoxification methods applied for reduction of aflatoxins by physical (cleaning, heating, irradiation, adsorption), chemical (chemical compound, ozonization) and biological (applying bacteria, yeast and nontoxigenic Aspergillus strains) methods in different foods from 2000 to 2015. Papers related to aflatoxin reduction by managing aflatoxins risks, using resistant crops varieties, and good agricultural practices and papers related to other aflatoxins (M1, M2) were excluded.